Application of Time-Weighted Association Rule Mining in Urban Water Resources Management - Jiang, Wenhao; Peng, Gaohui (International Journal of Computer Science and Information Technology, 2025)
Based on the water resource data of Zhengzhou City from 1999 to 2023, this study employs the time-weighted Apriori algorithm (with a decay factor of 0.85) combined with static-dynamic discretization preprocessing methods to mine dynamic association rules for three major water use types: integrated urban-rural water use, industrial water use, and agricultural water use. The results indicate that integrated urban-rural water use exhibits rigid growth, with its proportion rising from 18.4% to 67.8%; industrial water use has achieved "reduced volume with enhanced efficiency," with its proportion decreasing from 24.9% to 11.2%; and agricultural water use presents three coexisting patterns: stable, increasing, and decreasing. Water resource allocation strategies have shifted from "production-promotes-water-use" to "water-use-determines-production," with newly added water resources primarily allocated to urban-rural water use.